Analysis of Divorce Rate Determinants - Fojtíková, Kateřina; Frömmel, Tomáš; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
The thesis analyses the influencing factors of the divorce rate in the Czech Republic for the period of 1996–2016. It mainly focuses on the hypothesis about the longstanding belief that the divorce rate rises in periods of prosperity and the relationship between the divorce rate and religion. The time-series quarterly based data are used. As exogenous variables are selected the marriage rate, the growth rate of GDP, the unemployment rate, theeconomic activity of women, the average wage, the life expectancy of women, the university education of women, the rate of christening and the gender pay gap. The OLS empirical results confirm the assumed negative effect of the rate of christening on the divorce rate and do not support the unison movement of the business cycle and the divorce rate.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses